2018
DOI: 10.1038/s41598-018-28430-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of latent tuberculosis among Korean healthcare workers using whole-blood interferon-γ release assay

Abstract: Because healthcare workers (HCWs) are at high risk for tuberculosis (TB) infection, it is essential to research the prevalence of latent TB infection (LTBI) and to implement health interventions including early treatment of LTBI and TB infection control measures. The purpose of the study was to determine the prevalence and risk factors for LTBI using interferon-γ release assay (IGRA) among HCWs in South Korea. The cross-sectional study was carried in the National Health Insurance Service Ilsan Hospital, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 14 publications
2
16
0
1
Order By: Relevance
“…However, males had a higher incidence rate of PTB than females, suggesting that males were more likely to suffer from PTB among HCWs than females. It was consistent with the general population and other previous study on HCWs [21,22]. The national TB survey in China also demonstrated that the prevalence of TB in males of all age groups were higher than that in females (p < 0.05) [3].…”
Section: Discussionsupporting
confidence: 91%
“…However, males had a higher incidence rate of PTB than females, suggesting that males were more likely to suffer from PTB among HCWs than females. It was consistent with the general population and other previous study on HCWs [21,22]. The national TB survey in China also demonstrated that the prevalence of TB in males of all age groups were higher than that in females (p < 0.05) [3].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, many national policies and guidelines recommend that HCWs should be included in LTBI screening programs [56]. The prevalence of LTBI based on analyses using the interferon-gamma release assay (IGRA) is 16–18% for existing HCWs in Korea [78]. Since 2017, in accordance with the Tuberculosis Prevention Act, the government of Korea has paid for LTBI screening and treatment for HCWs [9].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we identified the distribution of the results, the changes in interpretation and the risks of increasing the degree of QFT-GIT. The positivity rate of the HCWs' initial IGRA test was 13.4%, which is slightly lower than that of 15.8-23.7% in other South Korean studies [17][18][19] and between that of 8.3-22.2% in low TB incidence countries [7-9, 11, 20]. Using the manufacturer's cutoff is simple to interpret but increases conversion and reversion.…”
Section: Discussionmentioning
confidence: 79%